Developmental divergence of sensory stimulus representation in cortical interneurons - Rahel Kastli (Nature Portfolio, 2020)
Sensory neuronal circuits adapt during maturation when animals start to actively interact with the external world. The authors reveal structural and functional rearrangements of the input cortical interneurons receive around the time the animals start active sensation.